THE INFLUENCE OF CULTURAL INTELLIGENCE ON SUSTAINABLE INNOVATION BEHAVIOR MEDIATED BY KNOWLEDGE SHARING AND MODERATE BY ORGANIZATION CULTURE - Murni Hernawati; Erny Tajib (International Journal Labs, 2024)
One of the keys to success for a company is the ability to maintain its sustainability in satisfying customers and stakeholders. The aim of this research is to answer the challenges and problems in maintaining business sustainability in the financial industry, including banking. This research includes four main variables, namely Cultural Intelligence, Sharing Knowledge, Organization Culture and Sustainable Innovation Behavior. The result finds that Employee's Cultural Intelligence has a significant effect on Sustainable Innovation Behavior and has no effect on Sharing Knowledge. However, the study shows that Organization Culture can play a role in moderating (strengthening) the influence of Employee's Cultural Intelligence by Sharing Knowledge. On the other hand, Organization Culture is unable to moderate the influence of Employee's Cultural Intelligence on Sustainable Innovation Behavior. Apart from that, it is also known that Sharing Knowledge is unable to mediate the influence of Employee's Cultural Intelligence on Sustainable Innovation Behavior. Companies are encouraged to maintain the condition where employees have the consciousness and understanding in the usage of Culture Knowledge when they interact with each other in diverse cultures and backgrounds, as well as to increase employees understanding of Organization Culture because it can strengthen the influence of Employee's Cultural Intelligence on knowledge sharing efforts